HSPB4/CRYAA Protect Photoreceptors during Retinal Detachment in Part through FAIM2 Regulation - Cagri G. Besirli; Madhu Nath; Jingyu Yao; Mercy Pawar; Angela M. Myers; David Zacks; Patrice E. Fort (MDPI AG, 2024)
Our previous study discussed crystallin family induction in an experimental rat model of retinal detachment. Therefore, we attempted to evaluate the role of α-crystallin in photoreceptor survival in an experimental model of retinal detachment, as well as its association with the intrinsically neuroprotective protein Fas-apoptotic inhibitory molecule 2 (FAIM2). Separation of retina and RPE was induced in rat and mouse eyes by subretinal injection of hyaluronic acid. Retinas were subsequently analyzed for the presence αA-crystallin (HSPB4) and αB-crystallin (HSPB5) proteins using immunohistochemistry and immunoblotting. Photoreceptor death was analyzed using terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end labeling (TUNEL) staining and cell counts. The 661W cells subjected to FasL were used as a cell model of photoreceptor degeneration to assess the mechanisms of the protective effect of αA-crystallin and its dependence on its phosphorylation on T148. We further evaluated the interaction between FAIM2 and αA-crystallin using a co-immunoprecipitation assay. Our results showed that α-crystallin protein levels were rapidly induced in response to retinal detachment, with αA-crystallin playing a particularly important role in protecting photoreceptors during retinal detachment. Our data also show that the photoreceptor intrinsically neuroprotective protein FAIM2 is induced and interacts with α-crystallins following retinal detachment. Mechanistically, our work also demonstrated that the phosphorylation of αA-crystallin is important for the interaction of αA-crystallin with FAIM2 and their neuroprotective effect. Thus, αA-crystallin is involved in the regulation of photoreceptor survival during retinal detachment, playing a key role in the stabilization of FAIM2, serving as an important modulator of photoreceptor cell survival under chronic stress conditions.